(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The quantity and quality of nutrients consumed by student’s can affect their balanced nutritional status, which will impact their developmental needs. School-aged children are experiencing a period of growth, requiring special attention from parents and the community, especially regarding nutrition and balanced diets. The purpose of this outreach program is for the students of SDN 1 Kadungora to have a higher awareness of the importance of a balanced diet to support optimal physical and cognitive development, and to build a healthier and highly competitive generation. Community service and outreach were conducted at SDN 1 Kadungora, Kadungora sub-district, Garut district, as a collaboration between KKN Thematic Group 18 of Garut University and Sunan Gunung Djati Islamic State University from Group 44, with a total of 44 students from 6th grade participating. The PKM program was carried out using direct outreach methods and the distribution of brochures. The results of the counselling show that before the counselling, 94.1% of students understood the definition of balanced nutrition, and after the counselling, this increased to 100%.